2020
DOI: 10.14692/jfi.16.1.21-29
|View full text |Cite
|
Sign up to set email alerts
|

Laju fotosintesis pada tanaman kelapa sawit terinfeksi karat daun Cephaleuros virescen

Abstract: Kejadian penyakit karat daun kelapa sawit yang disebabkan alga Cephaleuros virescens semakin meningkat di Indonesia. Kerugian karena penyakit ini pada tanaman kelapa sawit belum pernah diukur secara kuantitatif. Penelitian dilakukan untuk mengukur laju fotosintesis pada tanaman kelapa sawit umur 5 tahun dengan 3 kategori serangan yaitu ringan, sedang, dan berat. Hasil pengamatan di Kebun Kalianta  menunjukkan bahwa serangan karat daun dimulai dari pelepah bawah ke pelepah atas. Kejadian penyakit juga banyak te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
1
3
0
4
Order By: Relevance
“…The trend line models in Figures 9 and 10 from the monitoring data show that the results of the correlation analysis of the data variables are appropriate and varied, namely, the relationship is very weak to very strong (Table 3). The concordance of the analysis results (positive and negative correlations) in Table 3 was obtained based on the research report [17,15], namely an increase in plant age along with an increase in fruitset value and inversely proportional to the number of anthesis male inflorescences. The result of analysis in Table 3 shows that the fruitset value had a very strong correlation (0.945) with the plant age and a very weak correlation (0.017) with the male inflorescences anthesis per Ha.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…The trend line models in Figures 9 and 10 from the monitoring data show that the results of the correlation analysis of the data variables are appropriate and varied, namely, the relationship is very weak to very strong (Table 3). The concordance of the analysis results (positive and negative correlations) in Table 3 was obtained based on the research report [17,15], namely an increase in plant age along with an increase in fruitset value and inversely proportional to the number of anthesis male inflorescences. The result of analysis in Table 3 shows that the fruitset value had a very strong correlation (0.945) with the plant age and a very weak correlation (0.017) with the male inflorescences anthesis per Ha.…”
Section: Resultssupporting
confidence: 72%
“…The decline in the quality of FFB based on the value of the fruitset apart from the possibility of being caused by the soil type factor is also thought to be caused by the reduced population of pollinating insects of E. kamerunicus in the oil palm plantation area. Purba et al [3] and Susanto et al [17] reported a decrease in the population of E. kamerunicus followed by a lower value of the FFB fruitset. Further reported by [21] about the decline in the value of fruitset in North Sumatera by ± 16% after 17 years after the initial introduction of E. kamerunicus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Selain itu, karat daun juga dapat menyebabkan penutupan pada daun, sehingga luas permukaan daun yang aktif untuk proses fotosintesis menjadi berkurang (Sunpapao et al, 2017). Menurut (Susanto et al, 2020), penyakit karat daun dapat menyebabkan penurunan laju fotosintesis dan juga penutupan stomata pada daun.…”
Section: Pendahuluanunclassified